Hybrid perspectives: Muslim and secular discourses in French politics - Aprillia Firmonasari; Wening Udasmoro; Roberta Salzano (IAIN Salatiga, 2021)
Increased immigration, especially from Muslim-majority countries, has been broadly debated in French socio-political life. Frictions have been common between two groups: Muslims and non-Muslims who identify themselves as ‘defenders of secularism.’ At the same time, however, hybrid strategies have emerged in which Muslims and non-Muslims have sought to culturally and socially adapt themselves. Through a review of online French media published between 2017 and 2020, as understood using social constructivism, this study explores the groups’ construction of hybrid identities. Discourses were analyzed to identify their ideological schemes, utterances, references, and arguments, with linguistic analysis facilitated by NVIVO software. Analysis shows that the hybrid discourses of non-Muslim ‘defenders of secularism’ have been more prominent than those of Muslims. Furthermore, the narrative tendencies of these hybrid discourses indicate that non-Muslim groups have sought to promote diversity in religious practices in France, while Muslim groups have sought to integrate themselves into broader French society.